Técnica de clasificación cartográfica orientada a objetos para obtener una base de datos de usos de suelo de páramos, de Chimborazo. - J García, Víctor (2018)
The objective of this work was to develop a database on land uses in the páramos of the province of Chimborazo, using the object-based classification technique (GEOBIA) and high-resolution satellite images. To achieve the objective, high-resolution satellite images of Landsat 8 were captured, downloaded and pre-processed, and objects were identified and classified by grouping contiguous pixels that had similar pictorial characteristics. The results show that in 2016 there were 179233.48 hectares of páramo, of which 52,908.70 hectares belonged to páramo intervened (29.52%) and 126324.79 hectares of páramo not intervened (70.84%). The segmentation of the study area resulted in 79 quadrants with a total of 717280 objects. Each quadrant had an area of 10 km2. Thus, it was known that there are 43 quadrants with less than 30% of their surface covered by an ecosystem of páramo. Similarly, there are 8 quadrants where more than 50% of the area covered by the páramo ecosystem is intervened and there are 25 quadrants where more than 80% of its surface covered by the páramo ecosystem remains without intervention. This study shows that the object-based classification method (GEOBIA) and the use of satellite images can be used to evaluate vegetation cover and monitor the environment in the páramo ecosystem. Consequently, this study can be applied in other areas and can be useful as an effective tool for the regular monitoring necessary to support and create environmental sensitivity in relation to changes in vegetation in the páramo ecosystems